2020
DOI: 10.1111/nph.16984
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal dynamics of nonphotochemical quenching in Arabidopsis npq mutants assessed by solar‐induced fluorescence and reflectance measurements in the field

Abstract: This article is protected by copyright. All rights reserved • Solar-induced fluorescence (SIF) is highly relevant in mapping photosynthesis from remotesensing platforms. This requires linking SIF to photosynthesis and understanding the role of non-photochemical quenching (NPQ) mechanisms under field conditions. Hence, active and passive fluorescence were measured in Arabidopsis thaliana with altered NPQ in outdoor conditions. • Plants had mutations in either violaxanthin de-epoxidase (npq1) or PsbS protein (np… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 79 publications
2
20
0
Order By: Relevance
“…Meanwhile, the NPQ, an indicator of plant to disperse excess light energy in the form of heat to protect itself under adverse conditions, showed no significant differences under normal and dehydration conditions in control groups, while PwNAC11 OE lines showed increased NPQ values after drought treatment. These results verified the complete network of photoprotective mechanism in OE lines [38]. Recent studies revealed that the inhibition of light energy conversion could produce more excess excitation energy and promote the accumulation of ROS in plant [39].…”
Section: Pwnac11 Positively Regulates Drought Resistance In Transgenic Arabidopsissupporting
confidence: 77%
“…Meanwhile, the NPQ, an indicator of plant to disperse excess light energy in the form of heat to protect itself under adverse conditions, showed no significant differences under normal and dehydration conditions in control groups, while PwNAC11 OE lines showed increased NPQ values after drought treatment. These results verified the complete network of photoprotective mechanism in OE lines [38]. Recent studies revealed that the inhibition of light energy conversion could produce more excess excitation energy and promote the accumulation of ROS in plant [39].…”
Section: Pwnac11 Positively Regulates Drought Resistance In Transgenic Arabidopsissupporting
confidence: 77%
“…Third, the photoinhibitory component of NPQ, qI, is slowly reversible (within hours) and comprises processes related to either PSII core inactivation characterized by reduced maximal photochemical efficiency (Fv/Fm) [ 14 ] or slowly relaxing quenching, recently termed qH [ 3 ]. The qT component, which indicates state transitions, is triggered by low light conditions to balance the energy distribution of light energy between PSII and photosystem I (PSI) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, external conditions are rarely stable in natural environments, so plants need to continuously adjust to optimize the carbon uptake in these dynamic conditions (Kaiser et al, 2018). Different adjustments can be operated by plants depending on the time scale considered (Kono and Terashima, 2014): in the fast temporal scale, plants respond by regulating the mechanisms involved in photochemical (Kono and Terashima, 2014;Kaiser et al, 2018) and nonphotochemical processes (Acebron et al, 2021), activating the Calvin Cycle enzymes (Porcar-Castell et al, 2006) and moving their chloroplasts within the leaves (Kaiser et al, 2015); slower adjustments can then be due to the regulation of the stomata (Buckley, 2017;Vialet-Chabrand et al, 2017b;Matthews et al, 2018), the movements of the leaves within the canopy (as photonastic movements or due to the wind), and the adaptative adjustments in nitrogen and chlorophyll content (Posada et al, 2009;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%